Komunikasi Organisasi Kaj dalam Membangun Semangat Nasionalisme Umat Gereja Santo Bonaventura Pulomas - Narses Daniel Dandardana; Yogie Pranowo (UNIVERSITAS KALBIS, 2022)
Nationalism is a key point that required in the society and nation’s life. But, Nationalism of Indonesia in this modern age starting to eroded bit by bit because the lunge of Globalization, Modernization, religious differences, ethnicity / races differences, and political views differences in Indonesia. Jakarta Archdiocese is a part of the religious institution of Roman Catholic Church which has an authority in Jakarta, Tanggerang, and Bekasi which has a duties as a supervisor and a “Shepherd” for the church and the Catholics under the Jakarta Archdiocese authority. Then, it is the duty and responsibility of the KAJ as an organization that shade the Catholics of Jakarta to encourage the Catholics to rebuild their sense of Nationalism through external organizational communication. The purpose of this study is none other than to find out the form of KAJ communication and knowing the importance of a religious institution to reconstruct the nationalism of its people. This research was conducted with a qualitative approach with descriptive research methods to analyze external communication carried out by the KAJ to rebuild the nationalism of the Catholics by using the themes of Nationalism that have been determined in 2016 – 2020 ARDAS.